Dzielimy sie doświadczeniemThe use of the new irrigated bipolar radiofrequency ablation device (Cardioblate BP 2) in the surgical treatment of atrial fibrillation – practical aspects - Suwalski, Piotr; Suwalski, Grzegorz; Majstrak, Franciszek; Kurowski, Andrzej; Wilimski, Radosław; Suwalski, Kazimierz B. (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2006)
Atrial fibrillation is the most common arrhythmia and has a strong clinical impact on population, including patients after cardiac surgery. During the last decade rapid development in technique and technology in the surgical treatment of atrial fibrillation can be observed. Currently a new model of the irrigated bipolar radiofrequency device (Cardioblate BP 2) is entering the market. This paper is to share the experience after first Polish use of the device, especially in the practical and technical aspect. A 68-year-old patient with coronary artery disease and paroxysmal atrial fibrillation underwent surgical coronary revascularisation and pulmonary vein isolation using a new bipolar radiofrequency ablation device in the „off-pump” technique. The operation and postoperative course was uncomplicated. On the 2nd postoperative day atrial fibrillation onset was recorded, effectively treated with DC cardioversion. In 3 month-follow-up the patient has no angina symptoms. No arrhythmia was observed.